High-resolution Stratigraphy, Reservoir Geometry, and Facies Characterization of Cretaceous and Tertiary Turbidites from Brazilian Passive Margin Basins - Bruhn, Carlos H.L. (My University, 1993)
Two canyon-filling, coarse-grained turbidite systems have been studied, essentially at the oil-field scale, in immature passive margin basins of eastern Brazil. Three oil fields were chosen for detailed study from a group of over 120 turbidite oil fields distributed along the eastern Brazilian margin; Carapeba and Parga fields (tabular or lobate reservoirs, Coniacian/Santonian to early Maastrichtian, Campos basin), and Lagoa Parda field (channelized reservoirs, early Eocene, Espirito Santo basin). The three oil fields combined contain 162 wells (20 cored), with average spacing of 200- 500 m.
The Carapeba/Pargo turbidite system contains 181 - 198 coarse-grained turbidites, each with a thickness in the 0.5 - 12 m range. There are eight facies successions, 27 - 140 m thick. Each succession contains between 7 and 58 turbidites. Most of these successions become finer-grained upward and downcanyon, and their younger or more distal turbidites tend to become thinner-bedded and more discontinuous. The Carapeba/Pargo turbidite successions form 1 - 12 km wide, nonchannelized, tabular or lobate sandstone bodies. They were stacked in an overall retrogradational pattern for at least 20 km, recording the backfilling of the Carapeba/Pargo canyon.
The Lagoa Parda turbidite system contains unstratified, coarse-grained turbidites up to 6 m thick, with interbedded bioturbated mudstones and thin-bedded(< 70 cm), stratified, fine-grained sandstones. The coarse-grained facies fill 38 deeply-incised channels; these channel fills are 9 - > 50 m thick, 210 - > 1,050 m wide, and > 1 km long. The finergrained facies build asymmetrical levees that are higher and thicker on the left side (looking downstream) of their associated channels. Nine levee successions (up to 50 m thick) are associated with the 20 youngest channels. The overall Lagoa Parda turbidite system is characterized by channel fills that become narrower, thinner, and finer-grained upward. As a result of the common amalgamation of channel fills, and the partial preservation of levee deposits between channel fills, Lagoa Parda reservoirs show a complicated, multi-storied sand body geometry
Coarse-grained turbidite successions that fill canyons were developed in the eastern Brazilian margin during relative sea level falls that punctuated the overall transgressive setting of the late Cretaceous and early Tertiary. Only a few of the turbidite successions studied here can be correlated with global, eustatic sea level curves. Most of the relative sea level falls probably resulted from increased sediment supply, which, in turn, would have responded to tectonic reactivation in the source area and basin margin, and/or to climatically-controlled denudation rates in the source area.
Title: High-resolution Stratigraphy, Reservoir Geometry, and Facies Characterization of Cretaceous and Tertiary Turbidites from Brazilian Passive Margin Basins, Author: Carlos H. L. Bruhn, Location: Thode